High-grade endometrial stromal sarcoma displaying immunohistochemical expression of BCOR-A report of two cases of a novel tumor entity - Varsha Wagh; Santosh Menon; Amita Maheshwari; Sudeep Gupta; Kedar K Deodhar; Bharat Rekhi (Wolters Kluwer Medknow Publications, 2023)
Several defining molecular alterations have recently been identified underlying high-grade endometrial stromal sarcomas, such as YWHAE: NUTM2A/B fusions, ZC3H7B: BCOR fusions, and BCOR internal tandem duplication (ITD). BCOR is a useful immunohistochemical marker for identifying these tumors. A 37-year-old lady was presented with a 10-cm-sized tumor in the pouch of Douglas, involving the vaginal vault, bilateral adnexa, and peritoneum. A 53-year-old lady with a prior hysterectomy was presented with a 12-cm-sized tumor in the vault with abdominal deposits. Histopathological examination of both tumors revealed atypical cells comprising oval to spindle-shaped nuclei, a variable amount of myxoid stroma, and mitotic figures exceeding 10/10 high power fields. Immunohistochemically, the former tumor was diffusely positive for CD10, and the second tumor displayed patchy staining. Both tumors were positive for BCOR. Estrogen receptor (ER) showed variable staining in both tumors. By fluorescence in-situ hybridization (FISH), both tumors lacked YWHAE gene rearrangement. Both tumors had an aggressive clinical course, including extensive involvement This constitutes the first report of BCOR-positive high-grade sarcomas involving the female genital tract from our subcontinent. BCOR is a useful immunostain for identifying these relatively aggressive tumors. The differential diagnoses and the prognosis of these ultra-rare tumors are discussed herewith.